Antiseptic solutions modulate the paracrine‐like activity of bone chips: differential impact of chlorhexidine and sodium hypochlorite. (28th September 2015) - Sawada, Kosaku; Caballé‐Serrano, Jordi; Bosshardt, Dieter D.; Schaller, Benoit; Miron, Richard J.; Buser, Daniel; Gruber, Reinhard
Abstract Aim Chemical decontamination increases the availability of bone grafts; however, it remains unclear whether antiseptic processing changes the biological activity of bone. Materials and Methods Bone chips were incubated with four different antiseptic solutions including (1) povidone‐iodine (0.5%), (2) chlorhexidine diguluconate (0.2%), (3) hydrogen peroxide (1%) and (4) sodium hypochlorite (0.25%). After 10 min. of incubation, changes in the capacity of the bone‐conditioned medium (BCM) to modulate gene expression of gingival fibroblasts was investigated. Results Conditioned medium obtained from freshly prepared bone chips increased the expression of TGF‐β target genes interleukin 11 (IL11), proteoglycan4 (PRG4), NADPH oxidase 4 (NOX4), and decreased the expression of adrenomedullin (ADM), and pentraxin 3 (PTX3) in gingival fibroblasts. Incubation of bone chips with 0.2% chlorhexidine, followed by vigorously washing resulted in a BCM with even higher expression of IL11, PRG4 and NOX4. These findings were also detected with a decrease in cell viability and an activation of apoptosis signalling. Chlorhexidine alone, at low concentrations, increased IL11, PRG4 and NOX4 expression, independent of the TGF‐β receptor I kinase activity. In contrast, 0.25% sodium hypochlorite almost entirely abolished the activity of BCM, whereas the other two antiseptic solutions, 1% hydrogen peroxide and 0.5% povidone‐iodine, had relatively no impact respectively. Conclusion These in vitro findings demonstrate that incubation of bone chips with chlorhexidine differentially affects the activity of the respective BCM compared to the other antiseptic solutions. The data further suggest that the main effects are caused by chlorhexidine remaining in the BCM after repeated washing of the bone chips.